Reaching the In(Invisible): Addressing Barriers to Sexual Reproductive Healthcare of Lesbians, Bisexual Women and Sex Workers in Rivers State, Nigeria - Amadi Jennifer Chinoye (Journal of Women's Reproductive Health, 2024)
Access to sexual and reproductive healthcare for sexual minority women is essential to fulfilling their human rights. This qualitative study was conducted in Rivers State, Nigeria, with fifteen participants as key informants. The study addressed the barriers to the sexual and reproductive healthcare needs of lesbians, bisexual women and sex workers in Port Harcourt metropolis. To address these barriers, the study answered the research questions on what access barriers prevent lesbians, bi-women, and sex workers from adequate utilization of sexual and reproductive healthcare services and common mental health issues sexual minority women experience. The study found that the barriers that prevent sexual minority women from accessing sexual and reproductive healthcare services include limited sexual and reproductive health information on available services offered by the health facilities, prejudice from healthcare providers and lack of social acceptance. Common mental health issues experienced as a result of these limitations are self-doubt over sexual orientation, trauma from threats, and parental pressure over marriage. To mitigate these barriers, the study recommends training healthcare providers on inclusive sexual and reproductive healthcare and to eliminate stigma and discrimination to improve access. Additionally, an improvement in laws and increased agency of sexual minority women to minimize negative mental health experiences. Finally, it also recommends creating a social group for sexual minority women to share experiences, support each other and learn about their sexual and reproductive healthcare will minimise barriers.
Keywords: Sexual minority